Sarcopenia is associated with a greater risk of polypharmacy and number of medications: a systematic review and meta‐analysis. Issue 2 (13th February 2023) - Prokopidis, Konstantinos; Giannos, Panagiotis; Reginster, Jean Yves; Bruyere, Olivier; Petrovic, Mirko; Cherubini, Antonio; Triantafyllidis, Konstantinos K.; Kechagias, Konstantinos S.; Dionyssiotis, Yannis; Cesari, Matteo; Ibrahim, Kinda; Scott, David; et al.
Abstract: Polypharmacy in older adults is associated with multiple negative consequences that may affect muscular function, independently from the presence of medical conditions. The aim of this systematic review and meta‐analysis was to investigate the association of sarcopenia with polypharmacy and higher number of medications. A systematic literature search of observational studies using PubMed, Web of Science, Scopus and Cochrane Library databases was conducted from inception until June 2022. To determine if sarcopenia is associated with a higher risk of polypharmacy and increased number of medications, a meta‐analysis using a random‐effects model was used to calculate the pooled effects (CRD42022337539). Twenty‐nine studies were included in the systematic review and meta‐analysis. Sarcopenia was associated with a higher prevalence of polypharmacy (odds ratio [OR]: 1.65, 95% confidence interval [CI] [1.23, 2.20], I 2 = 84%, P < 0.01) and higher number of medications (mean difference: 1.39, 95% CI [0.59, 2.19], I 2 = 95%, P < 0.01) compared with individuals without sarcopenia. Using meta‐regression, a high variance was observed due to different populations (i.e., community‐dwelling, nursing home residents, inpatients, outpatients) for both outcomes of polypharmacy ( r = −0.338, SE = 0.1669, 95% CI [−0.67, −0.01], z = −2.03, P = 0.04) and number of medications ( r = 0.589, SE = 0.2615, 95% CI [0.08, 1.10], z = 2.25, P = 0.02). This systematic review and meta‐analysis reported a significantly increased risk of polypharmacy and higher number of medications in people with sarcopenia compared with individuals without this condition. Future research should clarify whether the specificity and number of medications is a direct contributor in accelerating the progression of muscle wasting and dysfunction contributing to sarcopenia in older adults.